Assessing blood flow, microvasculature, erythema and redness in hypertrophic scars: A cross sectional study showing different features that require precise definitions. Issue 5 (August 2017) - Jaspers, M.E.H.; Stekelenburg, C.M.; Simons, J.M.; Brouwer, K.M.; Vlig, M.; van den Kerckhove, E.; Middelkoop, E.; van Zuijlen, P.P.M.
Highlights: Blood flow, microvasculature and erythema are different hypertrophic scar features. Therefore, these outcome terms cannot be used interchangeably. 'Vascularization' is not an appropriate umbrella term for these scar features. Every scar feature requires a precise definition in research and clinical practice. Abstract: Background: In hypertrophic scar assessment, laser Doppler imaging (LDI), colorimetry and subjective assessment (POSAS) can be used to evaluate blood flow, erythema and redness, respectively. In addition, the microvasculature (i.e. presence of microvessels) can be determined by immunohistochemistry. These measurement techniques are frequently used in clinical practice and/or in research to evaluate treatment response and monitor scar development. However, until now it has not been tested to what extent the outcomes of these techniques are associated, whilst the outcome terms are frequently used interchangeably or replaced by the umbrella term 'vascularization'. This is confusing, as every technique seems to measure a specific feature. Therefore, we evaluated the correlations of the four measurement techniques. Methods: We included 32 consecutive patients, aged ≥18 years, who underwent elective resection of a hypertrophic scar. Pre-operatively, we performed LDI (measuring blood flow), colorimetry (measuring erythema) and the POSAS (subjective redness) within the predefined scar area of interest (∼1.5 cm). Subsequently, the scar was excised and the area of interest was sent for immunohistochemistry, to determine the presence of microvessels. Results: Only a statistically significant correlation was found between erythema values (colorimetry) and subjective redness assessment (POSAS) ( r = 0.403, p = 0.030). We found no correlations between the outcomes of LDI, immunohistochemistry and colorimetry. Conclusions: Blood flow, the presence of microvessels and erythema appear to be different hypertrophic scar features because they show an absence of correlation. Therefore, in the field of scar assessment, these outcome terms cannot be used interchangeably. In addition, we conclude that the term 'vascularization' does not seem appropriate to serve as an umbrella term. The use of precise definitions in research as well as in clinical practice is recommended.